Fabrication of 3D hydrogel platform for bullfrog skin derived collagen - Wong, Joey Hui Min (2019)
Wounds has placed a huge economic burden in the healthcare sector. In order to minimize the cost of wound care, it is crucial to implement efficient wound care management such as wound dressing to speed up the wound healing process. In general, collagen is commonly used in wound dressing. Their play an important role in attracting fibroblast to create extracellular matrix, keratinocytes to promote re-epithelization and endothelial cells to promote angiogenesis. Most of the commercially available collagen comes from mammalian sources such as bovine and porcine. However, there is a problem of religious restriction and risk of disease transmission in using mammalian derived collagen sources. As such, this project introduces bullfrog skin as an alternative source of collagen. Collagen derived from bullfrog skin are able to provide a safer source of collagen and does not have any religious issues. In this project, traditional acid solubilization method and novel blending method were used to extract collagen from bullfrog skin. Both methods were successful in extracting type 1 collagen. However, the novel blending method was able to extract collagen two times faster as compared to traditional acid solubilization method at a higher yield. In order to optimize the wound healing environment, collagen was fabricated into the form a hydrogel. Hydrogel is able to provide a moist wound healing environment which in turn helps to accelerate the wound healing process. In this study, salt solution was used to induce the gelation process. The concentration of the salt solution has an effect on the structural integrity of the gel. A higher salt concentration is able to provide a better structural integrity of the gel. To further improve the mechanical properties of the hydrogels, crosslinkers such as 1,4-Butanediol diglycidyl ether (BDE) and glutaralderhyde (GA) were added to improve the degradation stability of the hydrogel.